Implementasi Metode Pembelajaran Problem Based Learning Pada Mata Pelajaran Pendidikan Agama Islam - Rodiyah, Siti Kholidatur (Jurnal Riset Rumpun Agama dan Filsafat, 2022)
In choosing the right learning model, a teacher must pay attention to students' abilities and choose a learning model that can motivate them to learn and develop their potential so they can overcome problems in life. Problem-Based Learning is considered a learning model that can help students maximize their potential and develop skills in solving problems in everyday life. This study aims to critically analyze the application of problem-based learning models in the field of study of Islamic Religious Education. Through a literature study approach, this study focuses on a critical analysis of the basic concepts, principles, and procedures for applying the Problem-Based Learning method in learning Islamic Religious Education. The results of the research show that in order to implement PBL in the learning process, teachers should follow the procedures or implementation stages. The procedure for implementing PBL is divided into several steps, namely: problem orientation, organizing students to study (in groups), investigation or data collection, developing and presenting work results, and finally; evaluation and reflection.